THE CORRELATION BETWEEN ANXIETY AND STUDENT GPA & EPT SCORE DURING COVID 19 PANDEMIC - Masagus Abdullah Akhdan; Dyah Aminatun (fsip.teknokrat.ac.id, 2022)
One of the problems and inhibitions of students’ learning development is anxiety. Students’ in Indonesia learn online from home in an effort to limit social restrictions during the pandemic covid-19. From this online learning, there is also anxiety felt by students’. The purpose of this study is to find out what are the anxieties felt by students’ in online learning during this pandemic that have an correlation with their last GPA score and EPT (English proficiency test) score. This research was designed using quantitative correlational study with independent variables. The data of this study was taken from English Education Students’ of Universitas Teknokrat Indonesia and the sample obtained in this study was 39 students’ who take Quantitative Research class. The instruments used in collecting the data are questionnaire and the last GPA EPT score. Statistical analysis of Pearson product-moment correlation and SPSS software was used to find the correlation between the variables. The result of this study showed that there were negative correlation between anxiety and students’ GPA and EPT scores. The correlation was 0.925, and the t-table was lower than the T-test. As a result, it is entirely possible to conclude that anxiety has a statistically significant impact on student achievement.